Space for Public Democracy: The use of the hashtag #sahkanRUUTPKS on Twitter creates a New Social Movement - Helen Dian Fridayani (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
The aim of the research is to discover a new social movement that deviates from the social and political communication of the hashtag (#), validating the RUUTPKS on Twitter social media, which is now a democratic public space. Twitter contributes to the context of social movements by becoming a vehicle for people to communicate their demands. This study focuses on how Twitter social media becomes a platform for democratic public space from the demands of the hashtag (#) to legitimize the RUUTPKS which embodies a new social movement. The entire study methodology is a qualitative research method with a case study approach. In this study, data was collected using the literature review method, retrieval of documents on Twitter using the hashtag (#), and validation of the RUUTPKS using Ncapture Nvivo 12 Plus. The results of this study is voicing one's opinion on Twitter has a positive impact by giving birth to a genuine protest movement. The stages completed by each individual or group can have an impact on the group's movement. People's collective efforts for equality and social justice are reflected in social movements, as is the struggle to defend their identity and cultural heritage. Collective action and social movements have evolved into universal forces of historical systems and social activities. As a result, social movements and social activities exist in society and are frequently involved in conflicts and struggles over inequality, dominance, freedom, and social justice.